2020
DOI: 10.1186/s42077-020-00100-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal insular glioma–rare case report for a venous air embolism

Abstract: Background Venous air embolism (VAE) is a well-known entity in the field of neuroanesthesia, with established surgeries and positions where its occurrence is high. The insular cortex is a deep area within the lateral sulcus, and surgeries in this area are not reported to develop VAE. Case presentation A young male being operated on the insular cortex developed VAE, had cardiac arrest, was revived, and was extubated with no residual deficit due to the untoward event. Conclusions An anesthesiologist should a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Once VAE diagnosis is made, definitive therapy can be considered, especially if the patient is hemodynamically unstable or complicated by end-organ damage [ 5 ]. In case of hemodynamic instability, some studies have suggested that removing the air emboli from the right ventricle outflow tract, and hence maintaining circulation, can be made by increasing central venous pressures with intravenous fluids and patient positioning in Durant’s position (head low and right up) [ 1 ]. However, the ideal position assumed by an affected patient remains controversial as recent animal studies have demonstrated a lack of improvement despite relocating air bubbles to the apex of the right ventricle by means of postural changes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Once VAE diagnosis is made, definitive therapy can be considered, especially if the patient is hemodynamically unstable or complicated by end-organ damage [ 5 ]. In case of hemodynamic instability, some studies have suggested that removing the air emboli from the right ventricle outflow tract, and hence maintaining circulation, can be made by increasing central venous pressures with intravenous fluids and patient positioning in Durant’s position (head low and right up) [ 1 ]. However, the ideal position assumed by an affected patient remains controversial as recent animal studies have demonstrated a lack of improvement despite relocating air bubbles to the apex of the right ventricle by means of postural changes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ideal position assumed by an affected patient remains controversial as recent animal studies have demonstrated a lack of improvement despite relocating air bubbles to the apex of the right ventricle by means of postural changes [ 5 ]. Another strategy might be intermittent jugular venous compression, in order to prevent further air entry [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations